Comparison of sub-canopy topsoil properties between three woody plant species, a case study of the Baladeh Watershed, Mazandaran Province, Iran - Alireza Mohebali; Reza Erfanzadeh; Mohammad Jafari (Caspian Journal of Environmental Sciences)
Little information is available about the vegetation impact on soil, comparing the effects of different woody plant species on topsoil properties in subalpine degraded grasslands. Therefore, we studied the effects of three native woody plants with different structural canopies (evergreen needle-leaved vs. deciduous broad-leaved and cushion vs. free canopy) on the nutrient topsoil properties. We selected 20 sites as 20 replications in which all four woody species were found closed to each other in each site. Then soil samples were collected under the canopy of each woody species in June 2019 and transported to the laboratory for physico-chemical analyses. The results showed that generally, woody species differed in their effects on physico-chemical topsoil properties. So that, the needle-leaved evergreen Juniperus sabina exerted the most influence on soil properties compared to Berberis integerrima and Onobrychis cornuta (p < 0.05). Topsoil total organic carbon content was significantly highest under J. sabina and B. integerrima (3.30% and 3.07% respectively), while lowest under O. cornuta and herbaceous vegetation (2.61% and 2.23%, respectively). In addition, soil total nitrogen content was significantly highest under J. sabina and B. integerrima (0.18% and 0.17%, respectively), while lowest under O. cornuta and herbaceous vegetation (0.16% and 0.15%, respectively). The results of this study indicated that in sub-alpine grasslands, the presence and maintaining of woody species is important due to its positive role on substratum soil, considering in the rangeland improvement projects.